Implementasi Realitas Berimbuh pada Antarmuka Manusia-Mesin di Industri Proses - Wardana, Awang Noor Indra; Bachtiar, Yahya; Andriansyah, M Bobby; Salma, Rifdahlia (Jurnal Teknik Elektro, 2021)
Process industries such as oil refineries, petrochemical plants, and power plants require a human-machine interface system to monitor continuously. The operator usually carries out monitoring via a human-machine interface. However, it is difficult to know the condition of process equipment in real-time. The implementation of augmented reality allows engineers to visualize process equipment in real-time when conducting field inspections. The implementation of augmented reality at the human-machine interface to the fluid catalytic cracking process in an oil refinery is discussed in this paper. The design was started by developing a three-dimensional process equipment model using Autodesk Inventor. The result of the three-dimensional model then using Unity 3D software connected to the Vuforia Engine was implemented on a gadget into an augmented reality application. Data communication performance analysis was carried out using inferential statistics methods to test variations in service quality at levels 0, 1, and 2. The result of the Tukey test showed that the communication network latency value in level 2 was significantly higher than levels 0 and 1, which was 0.704±0.108 seconds. These results indicate that augmented reality can be implemented on human-machine interfaces by ensuring the quality of data communication services using Message Queue Telemetry Transport (MQTT) protocol at levels 0 or 1.